Italian in Switzerland: Statistical Data and Sociolinguistic Varieties (Gragoatá, 2021)
This contribution presents the different situations of Italian in the cantons of Ticino (where a gradual reduction in dialectophony is taking place) and Graubünden (where the dialect is being preserved), as well as the standardisation of Swiss Italian, which is taking place through the process of 'standard by mere usage' (AMMON, 2003, p. 2). A number of important theoretical concepts are brought up to date here in a very enlightening way: the concept of dilalie (BERRUTO, 1987) to describe the functional overlap between two varieties of a language, the pluricentricity of languages (CLYNE, 1989), models of standardisation of pluricentric languages (AMMON, 1989) and the representation of the bicentricity (AUER, 2005) of Italian (Italy and Switzerland).